(untitled) (Altre Modernità, 2025)
Mariacristina Cavecchi, The Art Gallery on Stage. New Vistas on Contemporary British Playwriting (London-New York, Bloomsbury Methuen Drama Engage, 2024, 290 pp. ISBN 9781350330702)